Improved mid-density genotyping platforms for breeding and mapping - CGIAR Research Program on Rice (2020)
Upgraded mid-density platforms have been implemented at several service providers. These contain a substantial increase in the breadth and depth of trait loci represented. Efforts are underway to improve discriminatory ability of genome-wide offerings.